PELATIHAN PEMBUATAN ECOENZYME BERBASIS LIMBAH BAWANG MERAH PADA KELOMPOK TANI TELAGA, DESA KEDISAN KINTAMANI BANGLI - Ramdhoani; Luh Putu Yuni Widyastuti; Ni Putu Eka Pratiwi (Jurnal Pepadu, 2025)
This community service program aimed to enhance the understanding and skills of members of the Kelompok Tani Telaga in Kedisan Village, Kintamani, Bangli, in managing shallot waste into an environmentally friendly product in the form of ecoenzyme. The partner’s main problem was the high volume of post-harvest shallot waste that had not been optimally utilized and posed a potential threat of environmental pollution. The implementation methods included socialization, hands-on training in ecoenzyme production, and mentoring for product quality evaluation. The results of the program showed an 80.83% increase in participants’ knowledge based on pre-test and post-test results, as well as the successful production of ecoenzyme that can be used as organic liquid fertilizer and biopesticide. In addition, the partners acquired new skills in processing agricultural waste into value-added products, thereby supporting sustainable agricultural practices in the area.